QUALITY PARAMETERS OF SOME NATURAL RUBBER (NR) CLONES INDIGENOUS TO NIGERIA. II. IONIC CONTENT, STABILITY AND DEGRADATION RESISTANCE OF NATURAL RUBBER (Biological Sciences - PJSIR, 2003)
The degradation resistance. protein content and the ionic analysis of the lattices of two local natural rubber (NR) clones (NNRL-Ilawe Ekiti) and NNRG-lgede Ekiti) and an  internation al natural  rnbber  clone (TJI-Malaysia)  have been  studied. The international clone (TJ1) was observed to be more resista nt to oxidative degradation than  the  local  clones.  The  resistance of NR to oxidative breakdown was improved by oxalic  and  phosphoric  acid  additives  and  ,,as fou nd  to  be related to absolute temperature by an Arrheni us type of equation  thereby  allowing  for  the  evaluation  of the  activation energy which is taken to be a measure of the degradation resistance of NR. The lat1ice of the inernational clone ([ fl) appears supe rior to the l at1i ces of the local clon es exa min ed , being of higher protein con tent, stability an d degradation resistance.